2008
DOI: 10.2320/matertrans.maw200830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Additions on Creep Properties of a Die-Cast AM50 Magnesium Alloy

Abstract: Tensile creep tests have been carried out for the die-cast AM50 + xCa (x ¼ 0:47, 0.95 and 1.72 mass pct) alloys in the temperatures between 423 and 523 K to elucidate the effect of calcium additions on creep properties for the AM50 alloy. The creep curve for the AM50 + xCa alloys is characterized by a minimum in the creep rate followed by an extended accelerating stage, and the decrease in creep rate during transient stage becomes pronounced with calcium concentration. The creep strengthening by calcium additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…AM50 + xCa (x ¼ 0:47, 0.95 and 1.72 mass%) die-cast alloys are superior in high temperature capability to AM50, as reported by Itoh et al 1) Also, the value of the dislocation density of AX52 (AM50 + 1.72Ca) die-cast alloy has been measured with transmission electron microscopy (TEM) techniques. The chemical composition of AX52 is shown in Table 1. 1)…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…AM50 + xCa (x ¼ 0:47, 0.95 and 1.72 mass%) die-cast alloys are superior in high temperature capability to AM50, as reported by Itoh et al 1) Also, the value of the dislocation density of AX52 (AM50 + 1.72Ca) die-cast alloy has been measured with transmission electron microscopy (TEM) techniques. The chemical composition of AX52 is shown in Table 1. 1)…”
Section: Introductionmentioning
confidence: 82%
“…To discuss the validity of the results obtained in this study and the method employed, values reported previously on the dislocation density of magnesium alloys 1,4) are listed in Table 4, together with the value obtained in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1(a), by using lever arm creep machines at 423 and 473 K under applied stresses that varied between 60 and 80 MPa. The prior deformation was interrupted at the time corresponding to the end of transient region for each creep condition, 12,13) by using compressed air under load followed by water quenching. The creep specimens with a gage length of 28 mm and a rectangular cross section of 6 Â 3 mm 2 shown in Fig.…”
Section: Methodsmentioning
confidence: 99%